Political communication strategy of the Prosperous Justice Party (PKS) to maintain victory in the 2024 general election for the Bandung City Regional People's Representative Council (DPRD) / Yusa Djuyandi … [et al.] - Djuyandi, Yusa Djuyandi; Azmi, Mohammad Fazrulzaman; Mustofa, Mustabsyirotul Ummah; Almushaf, Hasby Affan (Faculty of Communication & Media Studies, 2024)
The Prosperous Justice Party (PKS) was appointed to the Bandung City Regional People's Representative Council (DPRD) for the 2024–2029 term with the highest number of votes and seats in the general election of 2024. PKS became the dominant political party in Bandung City for the second time as a result of this election. The primary motivation for examining PKS's political communication strategy during the 2024 Election was the party's capacity to secure seats and votes in Bandung City. The method used in this study is qualitative. While secondary data was gathered via the media, primary data was collected through interviews. Based on the data analyzed, it can be concluded that PKS mostly uses direct political communication (door to-door) to spread its political message in Bandung City, in addition to engaging during the campaign, political communication with the public takes place during a five-year period. To establish and preserve emotional connections with the community, PKS cadres and supporters, as well as party elites (council members and party managers), play a crucial role. In addition to direct contact, political communication is also done indirectly through the use of outdoor media, the internet, and social media platforms that tell compelling narratives consistently.